Quantitative photoacoustics to measure single cell melanin production and nanoparticle attachment. (24th March 2015) - Bhattacharyya, Kiran; Eshein, Adam; Chandrasekhar, Anand; Viator, John A
Abstract: Photoacoustics can be used as a label-free spectroscopic method of identifying pigmented proteins and characterizing their intracellular concentration over time in a single living cell. The authors use a microscopic laser irradiation system with a 5 ns, Q-switched laser focused onto single cells in order to collect photoacoustic responses of melanoma cells from the HS936 cell line and gold nanoparticle labeled breast cancer cells from the T47D cell line. The volume averaged intracellular concentration of melanin is found to range from 29–270 mM for single melanoma cells and the number of gold nanoparticles (AuNP) is shown to range from 850–5900 AuNPs/cell. Additionally, the melanin production response to UV-A light stimulus is measured in four melanoma cells to find a mass production rate of 5.7 pg of melanin every 15 min.